Weather extremes and perinatal mortality – Seasonal and ethnic differences in northern Sweden, 1800-1895 - Schumann, Barbara; Häggström Lundevaller, Erling; Karlsson, Lena (PloS one, 2019)
Many studies have shown the impact of heat and cold on total and age-specific mortality, but knowledge gaps remain regarding weather vulnerability of very young infants. This study assessed the association of temperature extremes with perinatal mortality (stillbirths and deaths in the first week of life), among two ethnic groups in pre-industrial northern Sweden. We used population data of indigenous Sami and non-Sami in selected parishes of northern Sweden, 1800-1895, and monthly temperature data. Multiple logistic regression models were conducted to estimate the association of cold (<10th percentile of temperature) and warmth (>90th percentile) in the month of birth with perinatal mortality, adjusted for cold and warmth in the month prior birth and period, stratified by season and ethnicity. Perinatal mortality was slightly higher in Sami than in non-Sami (46 vs. 42 / 1000 live and stillbirths), but showed large variations across the region and over time. Both groups saw the highest perinatal mortality in autumn. For Sami, winter was a high-risk time as well, while for non-Sami, seasonality was less distinct. We found an association between exposure to cold and perinatal mortality among winter-born Sami [Odds ratio (OR) 1.91, 95% confidence interval (CI) 1.26-2.92, compared to moderate temperature], while there was little effect of cold or warmth during other seasons. Non-Sami, meanwhile, were affected in summer by warmth (OR 0.20, CI 0.05-0.81), and in autumn by cold (OR 0.39, CI 0.19-0.82). In this pre-industrial, subarctic setting, the indigenous Sami's perinatal mortality was influenced by extreme cold in winter, while non-Sami seemed to benefit from high temperature in summer and low temperature in autumn. Climate vulnerability of these two ethnic groups sharing the same environment was shaped by their specific lifestyles and living conditions.